Community Survey on Travel Preferences: What Can We Gain Insigths from Them in Early 2023? - Teresa Rebecca Hutabarat, Irene (Dinasti International Journal of Management Science, 2024)
The purpose of writing this article is to present an overview of society in early 2023 about their perspective on traveling. Apart from that, this research will also present significant others who are usually involved with the community when traveling. This research approach is descriptive, with the data collection method in the form of a survey consisting of 5W1H questions (What, When, Why, Who, Where, How) and given closed answer choices. The results of this study show that people prefer to travel communally, especially with colleagues, compared to going alone and traveling with colleagues is a preference in 2023